2011
DOI: 10.1074/jbc.m110.206615
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Gβγ in Tumorigenesis and Metastasis of Breast Cancer

Abstract: A growing body of evidence indicates that G protein-coupled receptors (GPCRs) are involved in breast tumor progression and that targeting GPCRs may be a novel adjuvant strategy in cancer treatment. However, due to the redundant role of multiple GPCRs in tumor development, it may be necessary to target a common signaling component downstream of these receptors to achieve maximum efficacy. GPCRs transmit signals through heterotrimeric G proteins composed of G␣ and G␤␥ subunits. Here we evaluated the role of G␤␥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 53 publications
(58 reference statements)
1
77
0
Order By: Relevance
“…Moreover, our previous work has already demonstrated that the regulation of G␤␥ signaling by WDR26 is critical for leukocyte migration (16). Recent work has shown that G␤␥ signaling is also involved in numerous pathological conditions such as heart failure and tumor growth and metastasis (5,33). It would be interesting to determine whether aberrant regulation of G␤␥ signaling by WDR26 contributes to these pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our previous work has already demonstrated that the regulation of G␤␥ signaling by WDR26 is critical for leukocyte migration (16). Recent work has shown that G␤␥ signaling is also involved in numerous pathological conditions such as heart failure and tumor growth and metastasis (5,33). It would be interesting to determine whether aberrant regulation of G␤␥ signaling by WDR26 contributes to these pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they directly interact with and modulate the activity of a long list of proteins including receptors, ion channels, and enzymes such as PLC, 2 phosphoinositide 3-kinases (PI3Ks), and G protein-coupled receptor kinase 2. Through these downstream targets, G␤␥ regulates diverse functions including immune and tumor cell migration (3)(4)(5), yeast cell mating (6), and heart rate (7).…”
mentioning
confidence: 99%
“…G␤␥ signaling is recognized to be important in several physiopathological conditions such as heart failure (42), tumorigenesis (43), cell migration and invasion (44), pharmacological tolerance and dependence (45), inflammatory processes (46), and several endocrine pathologies (47,48), among others. One of the first attempts at blocking the function of G␤␥ with selective peptides was developed for adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Conceivably, aberrant regulation of Gβγ signaling by WDR26 and RACK1 may contribute to tumor progression. Indeed, translocation suggest that active Gαi/o and/or Gβγ signaling is required for translocation.…”
mentioning
confidence: 99%